Seasonal variation and ecological significance of essential oil composition in Gymnanthemum amygdalinum (Delile) Sch. Bip. Ex Walp: A chemical and functional perspective - Bharathamma, Venkata; Narendar, Thappatla; Rama Devi, Bhukya (Current Botany, 2025)
The chemical makeup of essential oils extracted from Gymnanthemum amygdalinum stems varies seasonally, according to this study. Essential oils, noted for their ecological and economic applications, have dynamic chemical profiles that are impacted by ambient variables. Gas chromatography (GC) and mass spectrometry (GC-MS) were used to identify 33 chemicals, which included monoterpenes, oxygenated monoterpenes, sesquiterpenes, and oxygenated sesquiterpenes. Winter has the highest overall essential oil content (92.56%), with spring having the lowest (76.41%). Monoterpenes and oxygenated monoterpenes peaked during winter, implying enhanced enzymatic activity at colder temperatures. Sesquiterpenes were most plentiful in winter and rainy seasons, whereas oxygenated sesquiterpenes peaked during the rainy season. Key chemicals including limonene, methyl eugenol, and linalool were consistently detected. These findings highlight the importance of environmental conditions including temperature, humidity, and light in the biosynthesis and accumulation of volatile oils. This seasonal variability has implications for optimal harvesting and commercial use.